GCL hydration under simulated daily thermal cycles. Issue 4 (August 2011) - Kerry Rowe, R.; Rayhani, M.T.; Take, W.A.; Siemens, G.; Brachman, R.W.I.
Abstract : ABSTRACT: The hydration of three different geosynthetic clay liners (GCLs) subjected to daily thermal cycles was examined for a range of subsoil conditions. It was shown that daily thermal cycles can significantly decrease the equilibrium gravimetric moisture content of the GCL to as low as 15% of that under isothermal conditions in the worst case. For silty sand (SM) foundation soil with an initial gravimetric moisture content of 16%, the type of GCL had a significant effect on the daily variation in moisture content which ranged between 13% for one type of GCL and only 2% for another. The effect of these daily variations in moisture content on susceptibility to shrinkage is discussed. The initial moisture content and associated matric suction of the foundation soil was shown to have the dominant effect on GCL hydration. For GCLs over silty sand with initial moisture contents, w fdn, of 5, 10 and 16% and initial suction levels greater than their air entry value, the daily thermal cycles controlled GCL hydration at the end of the thermal cycle to moisture contents of between 14 and 30% and the GCL equilibrium moisture content was relatively insensitive to the initial foundation moisture content over this range. However when the foundation moisture content increased to w fdn = 21% (just below field capacity and the saturated moisture content) the GCL moisture contents increased to 113 to 127% (depending on GCL). Results are also reported for a GCL on poorly graded sand (SP) at 10% initial moisture content and the effect of the grading curve (and the related water retention curve) is discussed. The results of this study highlight the potential complexity of interpreting shrinkage of GCLs at the same site let alone at different sites.